Trauma‐Related Pain, Reexperiencing Symptoms, and Treatment of Posttraumatic Stress Disorder: A Longitudinal Study of Veterans. Issue 3 (12th May 2017) - Bartoszek, Gregory; Hannan, Susan M.; Kamm, Janina; Pamp, Barbara; Maieritsch, Kelly P.
Abstract : Research has demonstrated a strong positive association between posttraumatic stress disorder (PTSD) symptoms and physical pain. However, few studies have explored the impact of pain problems on the symptoms and treatment of PTSD, and results remain inconsistent. This longitudinal study examined whether trauma‐related and trauma‐unrelated pain differentially and uniquely predicted reexperiencing symptoms. We also examined whether levels of reexperiencing symptoms mediated the relationship between pain intensity and posttreatment symptoms of avoidance, numbing, and hyperarousal (ANH). Analyses were conducted using archival data from 99 treatment‐seeking veterans who reported the etiology and intensity of their pain and severity of PTSD symptoms pre‐ and posttreatment. Among veterans with trauma‐related pain, pain intensity (a) uniquely corresponded to greater posttreatment reexperiencing symptoms ( b  = 1.09), and (b) was indirectly predictive of ANH symptoms via the reexperiencing symptoms ( b  = 1.93). However, veterans with trauma‐unrelated pain evidenced no associations between pain intensity and reexperiencing ( b  = 0.04) or ANH symptoms ( b  = 0.06). We thus found that trauma‐related pain was indirectly related to poor PTSD treatment outcomes via reexperiencing symptoms. These findings offer additional insight into factors that may influence PTSD treatment outcomes for pain‐suffering trauma survivors.